Reduction of the Bitter Taste in Packaged Natural Black Manzanilla Olives by Zinc Chloride - Bautista-Gallego, Joaquin; Rodríguez-Gómez, Francisco; Romero-Gil, Verónica; Benítez-Cabello, Antonio; Arroyo-López, Francisco N.; Garrido-Fernández, Antonio (Frontiers in Nutrition, 2018)
The work assays the use of various concentrations of ZnCl2 (0.0–0.1%, w/v) in packaged natural black Manzanilla table olives. The transformations were followed for 4 months. The presence of Zn modified the leaching of total sugars (sucrose, glucose, fructose, and mannitol) into the brine, which decreased as the ZnCl2 content increased. Over the study, sucrose and glucose were exhausted while fructose, although consumed, left some final residues and the use of mannitol was limited. Titratable acidity was always gradually formed causing the subsequent pH decrease, which stabilized at ≈3.5. Acetic and mainly lactic acid were also formed during the assay, reaching the highest level of lactic acid in the 0.050% ZnCl2 treatment, followed by the Control. The acids were formed by lactic acid bacteria (LAB) (Lactobacillus pentosus, 39%, and Lactobacillus plantarum, 61%). However, the most outstanding Zn effect was found on the olive sensory characteristics: its presence markedly reduced the bitter notes, increased the overall appreciation, and the treatment containing 0.075% ZnCl2 had the highest scores in hardness, crunchiness, and overall appreciation. Therefore, the addition of ZnCl2 into packaged natural table olives may lead to healthy products with desirable sensory characteristics which, in turn, could promote consumption.